The Behaviors of Lending, Deposit Rates and Intermediation Premium of Pakistani Banks with Different Types of Ownership Structures - Nguyen, Chu V.; Ali, Muhammad Mahboob; Nedelea, Alexandru Mircea (Ecoforum Journal, 2017)
This study applies Enders and Siklos’ (2001) procedure to test for the long-run asymmetric co-integrating relationship and short-run dynamic Granger causality between Pakistani lending and deposit rates set by public, private, foreign, specialized, and all banks combined over the period January 2004 to December 2013. Terrorist activities on the money market plays negative role. The empirical results suggest a long-run asymmetric co-integration relationship between the rates. The Granger causality tests suggest bidirectional and asymmetric causality between lending and deposit rates set by Pakistani public and private banks, while the lending rates set by the country’s foreign, specialized and all banks combined are exogenous from their deposit rates. The unusually fast and overshot adjustments of the lending rates in response to increases in the intermediation premium of public banks are interpreted as graft maximization. The asymmetric and different nature of the Granger causalities exhibited by banks with different ownership structures should be of special interest for the Central Bank in formulating and implementing its countercyclical monetary policy and for corporations in determining their capital structures.